Exosomes: Origins and Therapeutic Potential for Neurodegenerative Disease - Sarko, Diana K.; McKinney, Cindy E. (Frontiers in Neuroscience, 2017)
Abstract: Exosomes, small lipid bilayer vesicles, are part of the transportable cell secretome that can be taken up by nearby recipient cells or can travel through the bloodstream to cells in distant organs. Selected cellular cytoplasm containing proteins, RNAs, and other macromolecules is packaged into secreted exosomes. This cargo has the potential to affect cellular function in either healthy or pathological ways. Exosomal content has been increasingly shown to assist in promoting pathways of neurodegeneration such as β-amyloid peptide (Aβ) accumulation forming amyloid plaques in the brains of patients with Alzheimer’s disease, and pathological aggregates of proteins containing α-synuclein in Parkinson’s disease transferred to the central nervous system via exosomes. In attempting to address such debilitating neuropathologies, one promising utility of exosomes lies in the development of methodology to use exosomes as natural delivery vehicles for therapeutics. Because exosomes are capable of penetrating the blood-brain barrier, they can be strategically engineered to carry drugs or other treatments, and possess a suitable half-life and stability for this purpose. Overall, analyses of the roles that exosomes play between diverse cellular sites will refine our understanding of how cells communicate. This mini-review introduces the origin and biogenesis of exosomes, their roles in neurodegenerative processes in the central nervous system, and their potential utility to deliver therapeutic drugs to cellular sites.